Dispersion of optical vortices in twisted elliptical-core optical fibers with torsional stresses - B.P. Lapin; E.V. Barshak; D.V. Vikulin; C.N. Alexeyev; M.A. Yavorsky (Компьютерная оптика)
In this paper, the dispersion of optical vortices (OVs) with a topological charge l >= 1 in twisted elliptical fibers (TEF) with torsional stresses (TS) is studied. Analytical expressions for polarization, topological, and hybrid dispersion are derived from the spectra of vortex modes in step- and gradient-index TEFs with TS. It is shown that in strongly twisted fibers with a gradient refractive index profile, new types of dispersion appear in comparison with the case of a step-index profile. The dependence of the dispersion of OVs on the material and geometrical parameters of the fiber is studied numerically. It is established that in step-index TEFs with TS, there is a spectral region near which all types of dispersion for OVs with l >= 1 take a near zero value. It is also demonstrated that for TEFs with a gradient profile, this regime is realized for strongly twisted strongly elliptical fibers.